Bernard Lewis, John Esposito and Gilles Keppel: A Comparative Study - Samiei, Mohammad (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Bernard Lewis, John Esposito and Gilles Keppel: A Comparative Study